Marketing Aspects of ISO System Implementation - Urbonavičius, Sigitas (Ekonomika, 2004)
The paper analyses the effects of the ISO system implementation and certification. It covers the aspects that are internal (managerial, personnel related) and external (mainly - marketing and sales related). Since there are differences between the ISO system implementation motivations and the actual benefits after its implementation, these two are analysed separately. In addition to a traditional mail survey, the author uses the technique of two qualitative interviews with every sample company, getting managerial opinions before the project (these mainly reflect motivations) and one year after the project (mainly reflecting benefits). The analysis is based on a sample of Lithuanian companies, comparing the findings with information from Lithuania and other countries.